Modes of HIV transmission among adolescents and young adults aged 10–24 years in Kenya - Ng’eno, Bernadette N (Int J STD AIDS, 2018)
Understanding how HIV is acquired can inform interventions to prevent infection. We constructed a risk profile of 10–24 year olds participating in the 2012 Kenya AIDS Indicator Survey and classified them as perinatally infected if their biological mother was infected with HIV or had died, or if their father was infected with HIV or had died (for those lacking mother’s data). The remaining were classified as sexually infected if they had sex, and the remaining as parenterally infected if they had a blood transfusion. Overall, 84 (1.6%) of the 5298 10–24 year olds tested HIV positive; 9 (11%) were aged 10–14 and 75 (89%) 15–24 years. Five (56%) 10–14 year olds met criteria for perinatal infection; 4 (44%) did not meet perinatal, sexual or parenteral transmission criteria and parental HIV status was not established. Of the 75 HIV-infected, 15 to 24 year olds, 5 (7%) met perinatal transmission, 63 (84%) sexual and 2 (3%) parenteral criteria; 5 (7%) were unclassified. Perinatal transmission likely accounted for 56% and sexual transmission for 84% of infections among 10–14 year olds and 15–24 year olds, respectively. Although our definitions may have introduced some uncertainty, and with the number of infected participants being small, our findings suggest that mixed modes of HIV transmission exist among adolescents and young people.